Shoulder rotators electro-mechanical properties change with intensive volleyball practice: A pilot study - Cornu, C.; Nordez, A.; Bideau, B. (International Journal of Sports Medicine, 2009)
This pilot study was designed to assess the incidence of high-level volleyball practice on muscle strength production and muscle activation during internal and external shoulder rotations. Seven professional and seven French amateur league volleyball players performed maximal isometric at three forearm angles, concentric and eccentric isokinetic internal and external shoulder rotations. The torque production and muscle activation levels of pectoralis major and infraspinatus were determined. Few significant differences were found for muscle activation and co-activation between amateur and professional volleyball players during both internal and external rotations. No significant difference in torque production was observed for shoulder internal rotation between professional and amateur volleyball players. Torque production was significantly higher during shoulder external rotation for amateur (46.58±2.62 N . m) compared to professional (35.35±1.17 N . m) volleyball players relative to isometric contractions, but it was not different during isokinetic efforts. The torque ratios for external/internal rotations were always significantly lower for professional (0.42±0.03 pooling isometric and concentric conditions) compared to amateur volleyball players (0.56±0.03 pooling isometric and concentric conditions). Those results emphasize that a high level of volleyball practice induces a strong external rotators deficit compared to sports such as swimming, baseball or tennis.